QUALITY AND PROCEDURAL STANDARDS OF PHARMACEUTICAL CARE DELIVERY IN PUBLIC AND PRIVATE HOSPITALS: DETERMINANTS OF SERVICE EXPERIENCE AMONG BPJS HEALTH BENEFICIARIES IN MEDAN - Muhammad Aditya Kurnia; Ahmad Syamsudin; Qian Dongfu; Hamid Gharibi; Niaz Ali; Wally Elijah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background. Indonesia has introduced the National Health Insurance program (BPJS) across both public and private hospitals. However, its implementation has been inconsistent, resulting in varying levels of service quality among hospitals. Notably, there is an absence of a unified national standard procedure, particularly within the pharmaceutical departments.Methods. This research used cross-sectional descriptive with survey mixed methods with aspects of quality of service depends variables independent divided into reliability, assurance, empathy, responsive, and tangibles affected relatively dependent variable as patient satisfaction with total of 384 respondents from public hospital and private hospital using multiple linear regression analysis and coefficient of determination (R2) to see strongest variables that most influenced via SPSS 24 software.Results. This study employed a cross-sectional descriptive design utilizing a mixed-methods survey approach. The independent variables, representing dimensions of service quality namely reliability, assurance, empathy, responsiveness, and tangibles were analyzed for their impact on the dependent variable, patient satisfaction. A total of 384 respondents from both public and private hospitals participated. Data analysis was conducted using multiple linear regression and the coefficient of determination (R²) to identify the most significant predictors influencing patient satisfaction.Conclusions. Patients demonstrated a preference for private hospitals due to their superior quality of healthcare services across all evaluated dimensions in this study. Private hospitals have effectively delivered high-standard pharmaceutical care, resulting in greater patient satisfaction. Consequently, it is advisable for the government to establish comprehensive national operational standards to regulate BPJS patient services uniformly.